Fabric sensors – modelling deformation in knitted fabrics - Miller, Katrina; Brown, Louise P.; McNally, Donal (2018)
Fabric sensors are made from knitted conductive yarn and can be used to measure extension in wearable technologies and composite structures. Wearable technologies have considerable potential in sport and medical applications, for example recording limb movement in injury monitoring or sporting technique analysis. The electrical resistance through the fabric varies with extension due to the change in contact area and contact force between yarns. The resistance can be interpreted using correlations with displacement to calculate the deformation experienced by the fabric sensor. This paper describes a study which works towards a realistic digital model of a single jersey knitted fabric sensor by considering a non-idealised monofilament yarn of varied cross-section in a dense knit geometry. Models are created using TexGen, software developed at the University of Nottingham, taking advantage of its facility to create complex cross-sections which vary along the length of the yarn. Subsequent finite element analysis using ABAQUS with small representative volume elements and periodic boundary conditions showed high peak stresses at the boundaries, possibly caused by the contact surface being split across the boundary. Subsequent simulations using larger numbers of stitches and with relaxed boundary conditions in the x-direction showed more realistic deformations including reduction in width and curling of the material, reducing the impact of the boundaries on the overall fabric simulation, but with significant computational cost. The results give an initial assessment of deformations and contact pressures, which will aid understanding of the non-linear response found in mechanical testing and improve knowledge of how the inter-yarn contact varies. This work lays the foundation for further work which will aim to improve the similarity between the digital knit geometry and the physical sample, model larger areas of knitted fabric, include residual stresses from manufacture and use a multifilament yarn model. Subsequently the much more complex knitting patterns produced by the manufacturer of these sensors will then be able to be modelled.